Evaluation of the effect of pulsed dye laser on chronic psoriatic plaque. (17th November 2018) - Elwan, Nagwa Mohammad; Gheida, Shereen Farouk; Hawwam, Soha Abdalla; Ahmed, Abeer Hussien
Abstract: Background: Psoriasis is one of the most prevalent immune mediated skin diseases. Selective vascular destruction by pulsed dye laser is considered one of effective laser treatments. Objective: Evaluation of the therapeutic effect of pulsed dye laser in treatment of chronic psoriatic plaque lesions and changes in human beta defensin-2(HBD-2) expression in the psoriatic patients before and after treatment, with correlation to the clinical improvement. Methods: Twenty patients with psoriatic plaque on right side treated by laser and another plaque on left side similar in size and its severity score served as control receiving no treatment. Each patient received 3–4 sessions of pulsed dye laser 595 nm. Follow up was done for three months. Results: There was statistically significant difference between the two psoriatic plaques (untreated and treated; A and B; p  = .004). There was significant decrease in HBD-2 expression after treatment. No recurrence was observed during follow up period. Conclusion: The pulsed dye laser is safe, effective, and tolerable treatment for resistant stable localized plaque psoriasis with minimal side effects and prolonged recurrence period.